Zika-Related Microcephaly and Its Repercussions for the Urinary Tract: Clinical, Urodynamic, Scintigraphic and Radiological Aspects - Rômulo Augusto Lucena de Vasconcelos; Ricardo Arraes de Alencar Ximenes; Adriano Almeida Calado; Celina Maria Turchi Martelli; Andreia Veras Gonçalves; Elizabeth Bailey Brickley; Thalia Velho Barreto de Araújo; Maria Angela Wanderley Rocha; Demócrito de Barros Miranda-Filho (Viruses, 2022)
Aims: Describing the urodynamic parameters of children aged 3 to 5 years with microcephaly related to congenital Zika syndrome and verifying the association with clinical, imaging and neurological characteristics. Methods: From October 2018 to March 2020, children with Zika-related microcephaly underwent urological, ultrasonographic and urodynamic evaluation. In selected cases, complementary exams such as urethrocystography and scintigraphy were performed. The children also underwent a complete neurological evaluation. To compare frequency between groups, we used Pearson’s chi-squared test or Fisher’s exact test. Results: This study evaluated 40 children, of whom 85% were 4 years old, and all had abnormalities on the urodynamic study, with low bladder capacity (92.5%) and detrusor overactivity (77.5%) as the most frequent findings. Only three children had ultrasound abnormalities, but no child had cystographic or scintigraphic abnormalities, and the postvoid residual volume was normal in 80% of cases. In spite of a frequency of 67.5% of intestinal constipation, there was no record of febrile urinary tract infection after the first year of life. All children presented severe microcephaly and at least one neurological abnormality in addition to microcephaly. The homogeneity of the children in relation to microcephaly severity and neurological abnormalities limited the study of the association with the urodynamic parameters. Conclusions: Urodynamic abnormalities in children aged 3 to 5 years with Zika-related microcephaly do not seem to characterize a neurogenic bladder with immediate risks for the upper urinary tract. The satisfactory bladder emptying suggests that the voiding pattern is reflex.